Inflammation Determines the Capacity of Allogenic Endothelial Cells to Regulate Human Treg Expansion - Cross, Amy Rachael (Front Immunol, 2021)
During allotransplantation, the endothelium acts as semi-professional antigen-presenting cells with the ability to activate proliferation and to promote differentiation of CD4(+)-T subsets. These abilities are dependent on the luminal expression of HLA class II antigens by microvascular endothelial cells, which is regulated by inflammatory cytokines. The upregulation of HLA-DR and HLA-DQ during rejection implies significant intragraft inflammation. Furthermore, the microvascular inflammation is an independent determinant for renal allograft failure. In this study, the potential of inflammation to modify endothelial regulation of peripheral CD4(+) Treg cells was examined. Microvascular endothelial cells were exposed to pro-inflammatory cytokines for varying durations before co-culture with PBMC from non-HLA matched donors. Proliferation and expansion of CD4(+)Treg and soluble factor secretion was determined. Early interactions were detected by phosphorylation of Akt. Video microscopy was used to examine spatial and temporal endothelial-CD4(+)T interactions. Highly inflammatory conditions led to increased endothelial expression of HLA-DR, the adhesion molecule ICAM-1, the costimulatory molecule PD-L1 and de novo expression of HLA-DQ. Treg differentiation was impaired by exposure of endothelial cells to a high level of inflammation. Neither IL-6, IL-2 nor TGFβ were implicated in reducing Treg numbers. High PD-L1 expression interfered with early endothelial cell interactions with CD4(+)T lymphocytes and led to modified TCR signaling. Blocking endothelial PD-L1 resulted in a partial restoration of Treg. The allogenic endothelial cell-mediated expansion of Treg depends on a critical threshold of inflammation. Manipulation of the PD-L1/PD-1 pathway or endothelial activation post-transplantation may promote or interfere with this intrinsic mechanism of allospecific Treg expansion.